5 years into augmented reality technology in education: Research trends, bibliometric study and its application to enhance visualization skills - Ali, Dayana Farzeeha (World Scientific and Engineering Academy and Society, 2021)
Augmented Reality technology allows users to interact with virtual objects integrated into the real world and real-time. Augmented Reality technology is considered a potential tool to promote the teaching and learning process. This study aims to identify the trends of publications related to Augmented Reality (AR) in education, bibliometric review of the studies as well as its application on enhancing students’ visualization skills in engineering education field. Thus, this study reviewed trends and bibliometric studies focusing on Augmented Reality (AR) in education for the past five years based on the Web of Science (WOS) database, and provide experimental results on the application of augmented reality technology to enhance visualization skills among engineering students. The result from this study proves that augmented reality shows an upward trends in education, as well as the experimental findings indicates positive results in enhancing visualization skills which is one of the reason why augmented reality is frequently used in education field as teaching and learning tools. This study will also provide researchers and educators with knowledge of the research trends of augmented reality in education. This paper will then highlight the most influential authors and countries in this research area as a reference for future researcher.